Persons with Disabilities Act 2008: a legal analysis on the protection of disabled rights / Nur Aqilah Pawancheek … [et al.] - Pawancheek, Nur Aqilah; Ahmad Mustaza, Maizatul Amalina; Kamarudin, Nurul Wahidah; Shaharuddin, Shahirah (2014)
Over the past decade, disabled persons have been increasingly found to be victims of exclusion from the mainstream society. In their fight for full equality, legislations and national policies governing disability rights have been repealed and formulated. Regardless, disabled persons continue to be regarded as a minority disadvantaged group. Their continuing challenges as a result of prejudice therefore necessitate research into this area. This paper focuses on the main disability legislation in Malaysia, the person with Disabilities Act 2008. With the aim of evaluating its degree of effectiveness in addressing disability rights issues, a number of studies from various countries are reviewed. The novelty of this paper is to look at the necessity of making several adjustments to the existing act to improve the welfare of disabled persons. Finally, this paper emphasises that more work needed to be done on the part of the government and society as a whole to patch up the loopholes present in the Act.